1974
DOI: 10.1159/000240642
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Glutathione Synthesis in the Neonate

Abstract: Red blood cell glutathione and the enzymes responsible for its synthesis in erythrocytes were measured in mothers and their offspring at time of delivery. γ-Glutamyl cysteine (GC) synthetase was the same in the two groups (neonates 0.313 and mothers 0.330 μmol GC formed/g Hb/min). The GSH synthetase was lower in umbilical cord blood than in maternal blood (cord blood 0.169 and maternal 0.214 μmol GSH formed/g Hb/min), even though the reduced GSH was greater in the former group than in the latter (cord blood 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Konrad et al [33] found higher GSH concentrations in cord erythrocytes than in normal nonneonatal blood and in nonneonatal blood with comparable reticulocytosis. Minnich et al [35] found higher GSH concentrations in cord blood of neonates than in maternal blood. The small but significant increase (+13%) in GSH levels found by us in term newborns with respect to adults confirms results of other studies reported in the literature [34,35].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Konrad et al [33] found higher GSH concentrations in cord erythrocytes than in normal nonneonatal blood and in nonneonatal blood with comparable reticulocytosis. Minnich et al [35] found higher GSH concentrations in cord blood of neonates than in maternal blood. The small but significant increase (+13%) in GSH levels found by us in term newborns with respect to adults confirms results of other studies reported in the literature [34,35].…”
Section: Discussionmentioning
confidence: 96%
“…Minnich et al [35] found higher GSH concentrations in cord blood of neonates than in maternal blood. The small but significant increase (+13%) in GSH levels found by us in term newborns with respect to adults confirms results of other studies reported in the literature [34,35]. Moreover, our data are the first ever to indicate simultaneously higher GSH and GSSG levels and antioxidant enzyme activities in RBC of premature newborns than in those of adults.…”
Section: Discussionmentioning
confidence: 96%
“…Red cells of newborn infants possess a higher level of adenosine triphosphate (ATP) (14,15), higher activity of many glycolytic enzymes and consume glucose at rates considerably faster than those observed in the cells of the normal adult (12,15,16). In spite of similar levels of 2,3-diphosphoglycerate (2,3-DPG) in the red blood cells, there are considerable differences between fetal and adult haemoglobins for oxygen affinity (13).…”
Section: Introductionmentioning
confidence: 99%
“…26 Minnich et al found higher GSH concentrations in cord blood of neonates than in maternal blood. 28 Frosali et al reported simultaneously higher GSH and GSSG levels and antioxidant enzyme activities in RBC of premature newborns than in those of adults. 20 All these results clearly show the great antioxidant resources of these cells against stressors associated with prematurity.…”
Section: Glutathione Recycling In Term and Preterm Newbornsmentioning
confidence: 97%